Association between tamoxifen and incidence of osteoporosis in Korean patients with ductal carcinoma in situ - Kim, Dooreh; Oh, Jooyoung; Lee, Hye Sun; Jeon, Soyoung; Park, Woo-Chan; Yoon, Chang Ik (Frontiers in Oncology, 2024)
Introduction The partial estrogen-agonist action of tamoxifen on bone receptors has beneficial effects on bone mineral density. However, in premenopausal women, the use of tamoxifen causes systemic estrogen depletion, which has detrimental effects on bone health. We aim to investigate the association between tamoxifen and osteoporosis in the real world using data from a longitudinal nationwide cohort of Korean patients. Methods Data were collected from the National Health Insurance claims database in South Korea. Osteoporosis was defined by diagnostic codes accompanying prescription data for osteoporosis. The cumulative incidence was analyzed by Kaplan–Meier survival curves and the risk factors were analyzed using a multivariable Cox proportional hazard regression model. Results Between 2009 and 2015, of the 4,654 women with ductal carcinoma in situ (DCIS) without prior osteoporosis, 2,970 were prescribed tamoxifen and 1,684 were not. A total of 356 DCIS survivors were later diagnosed with osteoporosis during a median follow-up period of 84 months. In the overall population, tamoxifen was associated with a low risk of osteoporosis, before and after propensity matching adjusted for age, operation type, and comorbidities (before matching, hazard ratio [HR]=0.69, 95% confidence interval [CI]=0.559–0.851, p<0.001; after matching, HR=0.664, 95% CI=0.513–0.858, p=0.002). In the subgroup analysis, findings were consistent in postmenopausal women but were not evident in the younger age group. Conclusion In a nationwide cohort study, a low risk of osteoporosis was associated with the use of tamoxifen. The protective effect of tamoxifen was more profound in older women and was not related to the incidence of osteoporosis in younger women.